Collective action problems in the contracting of public services: Evidence from the UK's Ministry of Justice. (September 2016) - Provost, Colin; Esteve, Marc
In this paper, we examine collective action problems in the UK government in the process of contracting public services to the private sector. In particular, we examine the Ministry of Justice (MoJ) and its evolution in contract monitoring as part of a larger effort of the government to join up departments in contract management. By analyzing MoJ's management of the electronic tagging contract with G4S and Serco, we show that a lack of coordination within the department and with other departments was a major reason for the overbilling by the two companies. Recent efforts to join up contract management efforts throughout government show promise in rectifying these contracting issues.